Features of formation of the cumulative effect of power loads in boys 7 years old - Cieślicka, Mirosława; Ivashchenko, Olga (Journal of Education, Health and Sport, 2017)
Purpose: To experimentally ground the technological approaches to evaluating training effects of primary schoolers’ power loads. Material and methods: To achieve the objectives outlined, the research used the following methods: analysis of scientific and methodological literature, pedagogical testing, modeling, pedagogical observation and experiment, methods of mathematical experiment planning (complete factorial experiment, 2k type), discriminant analysis. The participants in the study were 40 in boys 7 years old. Results: The training pattern affects the dynamics in the test results for the second grade boys. The test results can improve provided that the power load brings about significant changes after the training at each spot, after the training (immediate training effect), and twenty four hours after the power load (delayed training effect). The higher the dynamics is for the immediate and delayed training effects, the more significant are the improved power tests results observed after as few as three lessons. Conclusions: The discriminant function can be used to classify the training effects of the second grade boys’ power loads.